Honeybees (Apis mellifera) collect latex of Azores bellflowers (Azorina vidalii, Campanulaceae) - Weissmann, Julie A. (2015)
The Azores bellflower (Azorina vidalii (H.C.Wats.) Feer, synonym: Campanula vidalii H.C.Wats.) is a small shrub in the bellflower family, Campanulaceae, which is endemic to the Azores archipelago. Its habitats are coastal rocks and cliffs, often with elevated nitrogen levels (sewage water, rubbish) and close to settlements. Azorina is found on all nine islands of the Azores archipelago but is most common on the western islands of Flores and Corvo (Schaefer 2003). The pollination biology of Azorina is still a bit of a mystery: while flower morphology would fit best to bird pollination, birds have never been observed visiting its flowers and today’s avifauna of the archipelago does not include any obvious candidate species. The first author therefore performed an extensive field study in the summer of 2015, mainly on Corvo but also on Flores and Pico islands, in order to identify the pollinators of this enigmatic endemic. […].